Development of iPSC‐derived AD platforms for phenotypic screening. (20th December 2022) - Poon, Wayne; Zhou, Peng; Murchison, Angela; Noel, Christopher; Haag, Daniel; Wu, Ji; Huang, Tao
Abstract: Background: Human iPSC‐derived in vitro neural co‐culture systems have been used increasingly in drug discovery for neurological and neurodegenerative disorders. Method: Here we describe the development of iPSC‐derived platforms of AD that can be used to screen for preclinical targets and drug candidates. The foundation of these platforms utilizes a proprietary method for the generation of pure populations of NGN2‐based excitatory and ASCL1/DLX2 inhibitory neurons. Result: Transgenic overexpression of tau isoforms leads to prion‐like tau spreading that can be used to screen for compounds to mitigate tau propagation. Using this platform, we investigated how tau overexpression leads to neuron‐neuron tau transmission, alters neuron electrophysiology as assessed by MEA, and leads to the accumulation of key neuropathological tau biomarkers. In addition, we have developed co‐culture platforms that facilitate examination of the role of neuroinflammation on the development of key neuropathological hallmarks of AD. This platform can be used in conjunction with isogenic iPSCs to interrogate the mechanism by which genetic risk factors confer increased or decreased AD risk. Conclusion: Taken together, these phenotypic assays demonstrate the utility of NeuCyte platforms that can be applied to high‐throughput drug screening efforts for AD.